Pemberdayaan Dan Pengembangan Usaha Mikro, Kecil Dan Mengengah di Kabupaten Badung - Ida Ayu Putu Widiati; Ni Made Puspasutari Ujianti; Kade Richa Mulyawati (Fakultas Hukum, Universitas Warmadewa, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic position as a form of business activities capable of expanding job opportunities, providing broad economic services, playing a role in the process of equitability and increasing community income, encouraging economic growth, and contributing to the realization of national stability. Despite having shown its role in the regional economy, MSMEs in Badung Regency still face various obstacles and challenges, both internal and external, which lead to a weak competitive edge compared to other business players. This research aims to analyze the problems faced by MSMEs and formulate efforts for empowerment and development of MSMEs in Badung Regency. The research results indicate that empowerment efforts to address the problems of MSMEs in Badung Regency include education and training for human resources related to access to financing, product development, and strengthening marketing networks. Development efforts for MSMEs are directed at micro enterprises with the aim of increasing their scale to small enterprises by increasing the percentage of entrepreneurs in Badung Regency.